Constelation Of Power Behind Communication Presidential In Intolerance Issues (Critical Discourse Analysis of the President's Statement in the case of Meliana in Tanjungbalai) - Benny SUSETYO; Udi RUSADI; Mikhael DUA (Indonesia Strategic Sustainability, 2022)
Presidential communication has a role in carrying out the political function of the president as head of state or government. In practice, presidential communication pays attention to efforts to maintain power with ideological dominance through direct statements of the president, media quotes, or official social media accounts. This power is related to how the president manifests statements, attitudes, and actions as a practice of power carried out by political leaders. In the package of identity politics that is getting stronger, cases of intolerance are suspected to be very influential on the way the president conducts political communication. This study will focus on efforts to uncover hidden ideologies in presidential communications that contain power practices in cases of intolerance in Indonesia. Through a paradigm with an approach, this research uses Van Dijk's critical analysis method to find the presidential communication text related to the Meliana case in Tanjungbalai and to understand aspects of the president's cognition and social context in several related statements. This study concludes that the president's communication strategy has a double meaning behind the foundation of constitutionalism, embracing conflicting groups to get resources from their supporters and opposing groups. The president also used a political strategy to raise the issue in Tanjungbalai in what Walter Benjamin called a state of emergency with security and nationality but at the expense of marginalized groups.